2009
DOI: 10.1002/jbt.20264
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cytochrome P450 2C9 expression in primary cultures of human hepatocytes

Abstract: Cytochrome P450 2C9 (CYP2C9) expression is regulated by multiple nuclear receptors including the constitutive androstane receptor (CAR) and pregnane X receptor (PXR). We compared coregulation of CYP2C9 with CYP2B6 and CYP3A4, prototypical target genes for human CAR and PXR using human hepatocyte cultures treated for three days with the PXR activators clotrimazole, rifampin, and ritonavir; the CAR/PXR activator phenobarbital (PB); and the CAR-selective agonists CITCO, (6-(4-chlorophenyl)imidazo[2,1-beta][1,3]th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…The HepatoPac cultures show a higher and consistent response for both of the CYP2C genes compared with the monocultures. In the HepatoPac model we observed that a 3.5-fold change in mRNA and up to a 7-fold change in activity with phenobarbital, a dual PXR/CAR transactivator (Sahi et al, 2009). Phenobarbital showed the highest inductive response for CYP2C9 expression and activity in the HepatoPac model, perhaps owing to its dual activation of PXR and CAR.…”
Section: Discussionmentioning
confidence: 75%
“…The HepatoPac cultures show a higher and consistent response for both of the CYP2C genes compared with the monocultures. In the HepatoPac model we observed that a 3.5-fold change in mRNA and up to a 7-fold change in activity with phenobarbital, a dual PXR/CAR transactivator (Sahi et al, 2009). Phenobarbital showed the highest inductive response for CYP2C9 expression and activity in the HepatoPac model, perhaps owing to its dual activation of PXR and CAR.…”
Section: Discussionmentioning
confidence: 75%
“…Note the log scale for control CYP2B6 activity, whereas CYP1A2 and CYP2C9 are displayed on a linear scale. CYP2C9 expression is regulated, at least in part, by PXR (Sahi et al, 2009). A correlation analysis of fold induction of CYP1A2, CYP2C9, CYP2B6, and CYP3A showed no significant correlations (R 2 Յ 0.1; data not shown), implying minimal coregulation of these enzymes or an insufficient dynamic range to discern a correlation.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, it is possible that the extent of drug interactions after cotreatment with known PXR/CAR activators and CYP2C9 inducers such as rifampin or phenytoin or barbiturates might differ between individuals with the CYP2C9*1B versus other CYP2C9*1 genotypes. Although CYP2C9 is not highly induced in human hepatocytes by phenytoin (Sahi et al, 2009) (Fig. 7), hepatic CYP2C9 is also induced by rifampin, phenobarbital, and avasimibe (Chen et al, 2004;Sahi et al, 2009).…”
mentioning
confidence: 95%
“…Although CYP2C9 is not highly induced in human hepatocytes by phenytoin (Sahi et al, 2009) (Fig. 7), hepatic CYP2C9 is also induced by rifampin, phenobarbital, and avasimibe (Chen et al, 2004;Sahi et al, 2009). Moreover, CYP2C9 is among the three most highly induced CYPs in human duodenum in patients treated with clinical doses of oral rifampin (E. Schuetz, unpublished observation).…”
mentioning
confidence: 96%